METHOD OF ANALYSIS FOR DETERMINATION OF THE CHROMIUM (Cr) SPECIES IN WATER SAMPLES BY SPECTROPHOTOMETRY WITH DIPHENYLCARBAZIDE - Adam Wiryawan; Rurini Retnowati; Perry Burhan; Syekhfani Syekhfani (Journal of Environmental Engineering and Sustainable Technology, 2018)
Speciation of Chromium (Cr) is very important because of the toxicity of these metals depending on the oxidation number and its concentration is very low in the water system. Chromium occurs in the environment primarily in two valence states, trivalent Cr(III) and hexavalent Cr(VI). Chromium (III) is an essential micro-nutrients for the human body, while the Cr(VI) is highly toxic and carcino-gennic. Chromium(VI) in the water can be analyzed by spectrophotometry with diphenylcarbazide as reagent on pH=1 at maximum wavelength of 540 nm. The experimental result show that Cr(VI) can be analyzed using diphenylcarbazide in the concentration of 0.0015% and H3PO4 solution as acidic in 0.03 mol/L. The absorbance was measured at minutes 5 after preparation. There is interference from ion Fe(III) at least 6.0 ppm and this interference can be overcome by using 0.3 % NaF solution. The limit of detection of this method is -samples, mix of Cr(III) and Cr(VI), can be analyzed by using this method without oxidation by KMnO4 solution. While Cr(III)  in the artificial samples, mix of Cr(III) and Cr(VI), can be analyzed by using this method via oxidation by KMnO4 solution in the acidic media (H2SO4), the result of this analysis is the total concentration of Chromium. The concen-tration of Cr(III) can be calculate via subtract the total of Cr concentration by concentration of Cr(VI).Keywords: speciation, Cr(III), Cr(VI), spectropho-tometry, diphenylcarbazide, Fe(III), interference.